2018
DOI: 10.1093/femsec/fiy112
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, specificity, co-occurrence and hub taxa of the bacterial–fungal pollen microbiome

Abstract: Flower pollen represents a unique microbial habitat, however the factors driving microbial assemblages and microbe-microbe interactions remain largely unexplored. Here we compared the structure and diversity of the bacterial-fungal microbiome between eight different pollen species (four wind-pollinated and four insect-pollinated) from close geographical locations, using high-throughput sequencing of the 16S the rRNA gene fragment (bacteria) and the internal transcribed spacer 2 (ITS2, fungi). Proteobacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 82 publications
2
56
0
Order By: Relevance
“…Inference of co-occurrence networks is a computational method able to detect potential interactions between microbes based on their relative abundances in the samples [36]. This method is increasingly used to characterize the plant-associated microbiota, for example, in the rhizosphere [61,[67][68][69] or in the pollen habitat [70]. Here we showed that X. fastidiosa is potentially interacting with several species of bacteria and fungi in the leaf endosphere of Xf -infected "Leccino".…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Inference of co-occurrence networks is a computational method able to detect potential interactions between microbes based on their relative abundances in the samples [36]. This method is increasingly used to characterize the plant-associated microbiota, for example, in the rhizosphere [61,[67][68][69] or in the pollen habitat [70]. Here we showed that X. fastidiosa is potentially interacting with several species of bacteria and fungi in the leaf endosphere of Xf -infected "Leccino".…”
Section: Discussionmentioning
confidence: 78%
“…To identify significant patterns of correlated bacteria in the Xf -infected leaves of "Leccino" trees, the fungal and bacterial OTUs with at least 30 total reads and occurring in at least 3 samples were subjected to a co-occurrence analysis, using the software CoNet [103], which is available as add-on in Cytoscape 3.7 [104]. Non-rarefied, absolute abundance dataset was used, as recommended to avoid the false-positive issues when using relative abundance data [70]. A preliminary check of the dataset indicated a total of 1378 possible interactions.…”
Section: Correlation Of Co-occurrence Patterns and Network Analysismentioning
confidence: 99%
“…The pollen coat covering the outer layer of the pollen grain (the pollenkitt) is rich in lipids and carbohydrates (Heslop-Harrison & Heslop-Harrison, 1985;Pacini & Hesse, 2005), potentially creating an attractive habitat for microbial colonists. Indeed, recent investigations have demonstrated that the surface of pollen grains is colonised by a diverse community of microorganisms (F€ urnkranz et al, 2012;Ambika Manirajan et al, 2016;Kim et al, 2018;Manirajan et al, 2018); however, the impact of this microbiota on plant fitness is unknown. In nectar, colonisation by bacteria and yeast affects carbohydrate, amino-acid and secondary metabolite composition (Herrera et al, 2008;Peay et al, 2012;Vannette & Fukami, 2016;Rering et al, 2018), with negative or positive impacts on pollinator attraction (Vannette et al, 2012;Schaeffer et al, 2019).…”
Section: Antimicrobial Hypothesismentioning
confidence: 99%
“…Finally, the recent discovery of the complex pollen microbiota demands investigation of its role in pollination (Manirajan et al 2018, McFrederick & Rehan 2019. Indirect evidence points toward a role of pollen-colonising microorganisms in pollination.…”
Section: Future Directionsmentioning
confidence: 99%
“…As the main reward for their services, flowers offer nectar to the visiting pollinators providing them with sugars and other nutrients [17,18]. Given the nutrientrich nature of nectar and other floral rewards, microorganisms are commonly found in the flowers of a wide diversity of plant species worldwide [7,8,[19][20][21][22][23][24][25][26][27][28][29]. Flowerinhabiting microbes can alter the chemical composition of their habitat by consuming the available nutrients and/ or releasing metabolic by-products [30][31][32], which, in turn, may affect pollinators' foraging behavior and have an impact on the reproductive success of the plant (see below).…”
Section: Why Is It Worth Studying Flower-inhabiting Fungi?mentioning
confidence: 99%